Low-initial-viscosity-density controllable nano-micron particles for establishing deep longitudinal chemical interlayer of reservoir and preparation method of low-initial-viscosity-density controllable nano-micron particles
Through cross-linking polymerization and grinding technology of controllable nano microparticles with low initial viscosity density, an efficient longitudinal chemical separator is formed at the deep part of the reservoir, which solves the problem that the existing technology is difficult to establish a longitudinal chemical separator in the deep part of the reservoir, and achieves an efficient horizontal well segmented water control effect.
Patent Information
- Application Number
- CN202510274498.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-10
- Publication Date
- 2025-04-08
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
It is difficult for the prior art to establish longitudinal chemical partitions deep in the reservoir, resulting in the inability to effectively control the water in sections of horizontal wells.
Low initial viscosity density controllable nano microparticles are used to form high-strength elastomers through cross-linking polymerization, and grind into nano microparticles through high agitator and colloid milling, and the density and particle size are adjusted to achieve longitudinal expansion.
It is achieved to form an efficient longitudinal chemical separator deep in the reservoir, with a sealing rate greater than 92.5% and a compressive strength greater than 4.3MPa/m, effectively preventing fluid flow and achieving the purpose of horizontal wells to control water in sections.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of oilfield chemistry, and in particular relates to a low initial viscosity density controllable nano-micron particle for establishing a deep vertical chemical barrier interlayer in a reservoir and a preparation method thereof. Background Art
[0002] With the continuous advancement of oilfield development technology, more and more horizontal wells are being developed, especially in offshore oilfields. The contribution of horizontal wells to production exceeds 40%. However, due to the serious heterogeneity of the reservoir and the large oil-water viscosity ratio, the water content of horizontal wells has increased rapidly. The demand for oil stabilization and water control technology is becoming more and more urgent. Segmented water control is an effective means to solve the problem of water control in horizontal wells. In view of the actual situation that most offshore oilfields are completed with screen tubes for sand control, chemical isolation technology of the annulus outside the screen tube and mechanical segmented water control technology inside the screen tube have been established successively, solving the isolation problem between the screen tube and the well wall and inside the screen tube. The combination of the two technologies can effectively solve the problem of segmented water control in horizontal wells with natural interlayers. However, since most horizontal wells are developed within the layer, more than 90% of horizontal wells do not have natural interlayers. As a result, after the annulus in the horizontal well screen tube and between the screen tube and the well wall is isolated, the formation water will still flow from the reservoir, resulting in the inability to achieve effective segmented water control in horizontal wells. Therefore, it is necessary to establish artificial chemical interlayers to enhance the effect of staged water control measures in such horizontal wells, which is of great significance to the efficient development of horizontal wells. However, research in this field is still blank. Based on many years of research experience, the author proposed in the patent application number 202410247020.2 that 0.1%~0.3% hyperbranched polyacrylamide, 10%~30% urea-formaldehyde resin and 0.2%~0.6% cross-linking agent are injected around the wellbore, and a high-strength resin glue is formed as a chemical interlayer during the curing reaction. Due to the high viscosity of the material after injection and the non-adjustable density, it is difficult to form a longitudinal interlayer, and the curing reaction is fast, so it can only act on the area near the wellbore and cannot enter the deep reservoir to establish a longitudinal chemical interlayer in the deep reservoir.
[0003] Therefore, there is an urgent need in the art for a material for establishing a vertical chemical barrier interlayer deep in a reservoir. Summary of the invention
[0004] The present invention is proposed to solve the problems existing in the prior art, and its purpose is to provide a low initial viscosity density controllable nano-micron particle and a preparation method thereof for establishing a deep vertical chemical barrier interlayer in a reservoir.
[0005] The present invention is achieved through the following technical solutions: A low initial viscosity density controllable nano-micron particle for establishing a deep vertical chemical barrier interlayer in a reservoir, wherein the components of the low initial viscosity density controllable nano-micron particle and the mass percentage of each component are: Strength control agent 20%~30%; Cross-linking agent 0.05%~0.2%; Initiator 0.1%~0.4%; Density regulator 1%~10%, Remaining amount of water for preparation of liquid.
[0006] In the above technical solution, the strength control agent is a mixture of starch and acrylamide in a mass ratio of 1:1 to 1:3; the strength control agent needs to be gelatinized at 80°C for 10 minutes before use.
[0007] In the above technical solution, the cross-linking agent is any one or more of phenolic resin prepolymer, chromium acetate or N,N-methylenebisacrylamide.
[0008] In the above technical solution, the initiator is any one or more of ammonium persulfate, acrylate or dibenzoyl peroxide.
[0009] In the above technical solution, the density regulator is any one or more of nano calcium carbonate powder, sodium chloride or hollow glass microspheres.
[0010] In the above technical solution, the liquid preparation water is tap water or on-site injected water.
[0011] A method for preparing low initial viscosity density controllable nano-micron particles for establishing a vertical chemical barrier interlayer in a deep reservoir, comprising the following steps: (I) under stirring conditions, adding the strength control agent to the heated liquid preparation water in proportion to form a paste-like fluid; (II) under stirring, adding the crosslinking agent, initiator and density regulator in proportion to the paste-like fluid of step (I) in sequence and fully dissolving them; (III) subjecting the mixture obtained by fully dissolving the mixture in step (II) to a cross-linking polymerization reaction to form a high-strength elastomer; (IV) The high-strength elastomer is crushed by a high-speed agitator and further ground by a colloid mill to obtain low initial viscosity and controllable nano-micron particles.
[0012] In the above technical solution, the temperature of the heated preparation water in step (I) is 80° C., the stirring speed is 400 rad / min, and the stirring time is 10 min.
[0013] In the above technical solution, the stirring speed of step (II) is 400 rad / min.
[0014] In the above technical solution, the temperature of the cross-linking polymerization reaction in step (III) is 80° C., and the reaction time is 8 h to 12 h.
[0015] The beneficial effects of the present invention are: The present invention provides a low initial viscosity density controllable nano-micron particle for establishing a deep vertical chemical barrier interlayer in a reservoir and a preparation method thereof. The low initial viscosity density controllable nano-micron particle of the present invention is suitable for oil reservoirs with a temperature of 50°C to 120°C and a formation water mineralization of ≤25×10 4 mg / L, which is applicable to a wide range of oil reservoirs; the particle size can be adjusted in the range of nanometers to micrometers by adjusting the parameters of the colloid mill; the viscosity of the working fluid is 1.1mPa·s~3mPa·s, the initial viscosity is low, and it is easy to enter the deep reservoir; the particle density can be adjusted to 0.81g / cm by using the density regulator 3 ~1.19g / cm 3 The controllable range is conducive to the longitudinal distribution of particles and the formation of longitudinal chemical interlayers. The low initial viscosity density controllable nano-micron particles of the present invention accumulate, bridge and adhere to each other in the reservoir to form a longitudinal chemical interlayer in the deep part of the reservoir. The plugging rate is greater than 92.5%, and the compressive strength is greater than 4.3MPa / m, which can effectively prevent the fluids on both sides of the longitudinal chemical interlayer from flowing into each other. DETAILED DESCRIPTION
[0016] In order to enable persons skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention is further described below through specific implementation methods.
[0017] A method for preparing low initial viscosity density controllable nano-micron particles for establishing a vertical chemical barrier interlayer in a deep reservoir comprises the following steps: (I) Weigh the prepared water in proportion and pour it into a beaker. Place the beaker in a constant temperature water bath at 80°C. Place a stirrer in the beaker and set the stirrer speed to 400 rad / min. Start stirring. (II) Weigh starch and acrylamide in proportion, add them slowly and evenly into the stirring liquid water, and keep stirring for 10 minutes to form a paste-like fluid; (III) while continuing to stir, add the cross-linking agent, initiator and density regulator in order according to the proportion; (IV) After the components are stirred and dissolved, they are placed in an oven at 80°C to undergo a cross-linking polymerization reaction for 8h to 12h to form a high-strength elastomer; (V) The high-strength elastomer is ground into powder using a high-speed agitator, and the small rubber particles are further ground into nano-micron particles using a colloid mill.
[0018] The low initial viscosity density controllable nano-micron particle component of the present invention is composed of a strength control agent, a cross-linking agent, an initiator, a density regulator, and a liquid water. The components are cross-linked and polymerized to form a high-strength elastomer, and then the high-strength elastomer is ground into low initial viscosity density controllable nano-micron particles by a high-speed stirrer and a colloid mill. The strength control agent is a mixture of starch and acrylamide, and the two work together to react with the cross-linking agent and the initiator to cross-link and polymerize to form a high-strength elastomer; the density regulator can increase or decrease the density of the high-strength elastomer, so that the low initial viscosity density controllable nano-micron particles can be better distributed along the longitudinal direction of the reservoir, which is conducive to the formation of a longitudinal chemical partition; the high-strength elastomer can be crushed by a high-speed stirrer, and then according to the needs of the reservoir, by adjusting the parameters of the colloid mill, the shredded small particle rubber blocks are further ground into particles of the target particle size, taking into account the particle injectability and reservoir matching, ensuring that the particles are stacked, bridged and mutually adhered in the deep reservoir, and forming a longitudinal chemical barrier interlayer in the deep reservoir.
[0019] Example 1 Take 76.25g of tap water, add it to a beaker, place it in a water bath at 80℃, slowly and evenly add 7.5g of starch and 15g of acrylamide while stirring, stir and mature for 10min, then add 0.05g of N,N-methylenebisacrylamide, 0.2g of ammonium persulfate, and 1g of nano calcium carbonate powder in sequence while stirring, continue to stir to make it uniform, and its composition by mass fraction is 22.5% of strength control agent, 0.05% of N,N-methylenebisacrylamide, 0.2% of ammonium persulfate, 1% of nano calcium carbonate powder, and 76.25% of tap water. Then pour the above prepared liquid into a bottle, place it in an oven at 80℃, react for 12h to form a high-strength elastomer, then use a high-speed stirrer to crush it, and use a colloid mill to further grind it to form nano-micron particles. The nano-micron particles have a particle size of 81nm and a density of 1.09g / cm 3 When the mass fraction of tap water is 2%, the initial viscosity of the nano-micron particles is 1.1 mPa·s.
[0020] Example 2 Take 66.55g of tap water, add it to a beaker, place it in a water bath at 80℃, slowly and evenly add 7.5g of starch and 22.5g of acrylamide while stirring, stir and mature for 10min, then add 0.05g of N,N-methylenebisacrylamide, 0.4g of ammonium persulfate, and 3g of nano calcium carbonate powder in sequence while stirring, continue to stir to make it uniform, and its composition by mass fraction is 30% strength control agent, 0.05% of N,N-methylenebisacrylamide, 0.4% of ammonium persulfate, 3% of nano calcium carbonate powder, and 66.55% of tap water. Then pour the above prepared liquid into a bottle, place it in an oven at 80℃, react for 8h to form a high-strength elastomer, then use a high-speed stirrer to crush it, and use a colloid mill to further grind it to form nano-micron particles. The nano-micron particles have a particle size of 505nm and a density of 1.11g / cm 3 When the mass fraction of tap water is 2%, the initial viscosity is 1.5 mPa·s.
[0021] Example 3 Take 74.8g of tap water, add it to a beaker, place it in a water bath at 80℃, slowly and evenly add 10g of starch and 10g of acrylamide while stirring, stir and mature for 10min, then add 0.1g of N,N-methylenebisacrylamide, 0.1g of ammonium persulfate, and 5g of nano calcium carbonate powder in sequence while stirring, continue to stir to make it uniform, and its composition by mass fraction is 20% strength control agent, 0.1% of N,N-methylenebisacrylamide, 0.1% of ammonium persulfate, 5% of nano calcium carbonate powder, and 74.8% of tap water. Then pour the above prepared liquid into a bottle, place it in an oven at 80℃, react for 12h to form a high-strength elastomer, then use a high-speed stirrer to crush it, and use a colloid mill to further grind it to form nano-micron particles. The nano-micron particles have a particle size of 505nm and a density of 1.13g / cm 3 When the mass fraction of tap water is 2%, the initial viscosity is 1.6 mPa·s.
[0022] Example 4 Take 74.8g of on-site injection water (total mineralization is 25×10 4mg / L, containing calcium and magnesium ion concentrations of 5000mg / L), add it to a beaker, place it in a water bath at 80℃, slowly and evenly add 10g starch and 10g acrylamide while stirring, stir and mature for 10min, then add 0.1g N,N-methylenebisacrylamide, 0.1g ammonium persulfate, and 5g nano calcium carbonate powder in sequence while stirring, continue to stir to make it uniform, and its composition is calculated by mass fraction as strength control agent 20%, N,N-methylenebisacrylamide 0.1%, ammonium persulfate 0.1%, nano calcium carbonate powder 5%, and on-site injection water 74.8%. Then pour the above-prepared liquid into a bottle, place it in an oven at 80℃, react for 12h to form a high-strength elastomer, then use a high-speed stirrer to crush it, and use a colloid mill to further grind it to form nano-micron particles. The nano-micron particles have a particle size of 813nm and a density of 1.14g / cm 3 When the mass fraction of the injected water was 2%, the initial viscosity was 1.4 mPa·s.
[0023] Example 5 Take 66.7g of tap water, add it to a beaker, place it in a water bath at 80℃, slowly and evenly add 10g of starch and 15g of acrylamide while stirring, stir and mature for 10min, then add 0.1g of N,N-methylenebisacrylamide, 0.2g of ammonium persulfate, and 8g of nano calcium carbonate powder in sequence while stirring, continue to stir to make it uniform, and its composition by mass fraction is 25% strength control agent, 0.1% of N,N-methylenebisacrylamide, 0.2% of ammonium persulfate, 8% of nano calcium carbonate powder, and 66.7% of tap water. Then pour the above prepared liquid into a bottle, place it in an oven at 80℃, react for 12h to form a high-strength elastomer, then use a high-speed stirrer to crush it, and use a colloid mill to further grind it to form nano-micron particles. The nano-micron particles have a particle size of 5μm and a density of 1.16g / cm 3 When the mass fraction of tap water is 2%, the initial viscosity is 2.1 mPa·s.
[0024] Example 6 Take 59.55g of tap water, add it to a beaker, place it in a water bath at 80℃, slowly and evenly add 10g of starch and 20g of acrylamide while stirring, stir and mature for 10min, then add 0.15g of N,N-methylenebisacrylamide, 0.3g of ammonium persulfate, and 10g of nano calcium carbonate powder in sequence while stirring, continue to stir to make it uniform, and its composition by mass fraction is 30% strength control agent, 0.15% of N,N-methylenebisacrylamide, 0.3% of ammonium persulfate, 10% of nano calcium carbonate powder, and 59.55% of tap water. Then pour the above prepared liquid into a bottle, place it in an oven at 80℃, react for 10h to form a high-strength elastomer, then use a high-speed stirrer to crush it, and use a colloid mill to further grind it to form nano-micron particles. The nano-micron particles have a particle size of 24μm and a density of 1.19g / cm 3 When the mass fraction of tap water is 2%, the initial viscosity is 2.5 mPa·s.
[0025] Example 7 Take 59.6g of tap water, add it to a beaker, place it in a water bath at 80℃, slowly and evenly add 15g of starch and 15g of acrylamide while stirring, stir and mature for 10min, then add 0.2g of N,N-methylenebisacrylamide, 0.2g of ammonium persulfate, and 10g of hollow glass microspheres in sequence while stirring, continue to stir to make it uniform, and its composition is calculated by mass fraction as 30% strength control agent, 0.2% of N,N-methylenebisacrylamide, 0.2% of ammonium persulfate, 10% of hollow glass microspheres, and 59.6% of tap water. Then pour the above prepared liquid into a bottle, place it in an oven at 80℃, react for 12h to form a high-strength elastomer, then use a high-speed stirrer to crush it, and use a colloid mill to further grind it to form nano-micron particles. The nano-micron particles have a particle size of 43μm and a density of 0.81g / cm 3 When the mass fraction of tap water is 2%, the initial viscosity is 3mPa·s.
[0026] Example 8 Take 76.3g of tap water, add it to a beaker, place it in a water bath at 80℃, slowly and evenly add 7.5g of starch and 15g of acrylamide while stirring, stir and mature for 10min, then add 0.1g of chromium acetate, 0.1g of dibenzoyl peroxide, and 1g of nano calcium carbonate powder in sequence while stirring, continue stirring to make it uniform, and its composition by mass fraction is 22.5% of strength control agent, 0.1% of chromium acetate, 0.1% of dibenzoyl peroxide, 1% of nano calcium carbonate powder, and 76.3% of tap water. Then pour the above prepared liquid into a bottle, place it in an oven at 80℃, react for 12h to form a high-strength elastomer, then use a high-speed stirrer to crush it, and use a colloid mill to further grind it to form nano-micron particles. The nano-micron particles have a particle size of 51μm and a density of 1.09g / cm 3 When the mass fraction of tap water is 2%, the initial viscosity is 1.2 mPa·s.
[0027] Example 9 Take 76.2g of tap water, add it to a beaker, place it in a water bath at 80℃, slowly and evenly add 7.5g of starch and 15g of acrylamide while stirring, stir and mature for 10min, then add 0.2g of phenolic resin prepolymer, 0.1g of acrylate, and 1g of nano calcium carbonate powder in sequence while stirring, continue stirring to make it uniform, and its composition by mass fraction is 22.5% of strength control agent, 0.2% of phenolic resin prepolymer, 0.1% of acrylate, 1% of nano calcium carbonate powder, and 76.2% of tap water. Then pour the above prepared liquid into a bottle, place it in an oven at 80℃, react for 12h to form a high-strength elastomer, then use a high-speed stirrer to crush it, and further grind it with a colloid mill to form nano-micron particles. The nano-micron particles have a particle size of 48μm and a density of 1.09g / cm 3 When the mass fraction of tap water is 2%, the initial viscosity is 1.1 mPa·s.
[0028] The samples prepared in Example 1 were tested: Take two artificial cores, denoted as 1# and 2#, and measure their permeability k1 before plugging after water drive until the pressure is stable. Then inject 0.3V reversely. p After adding the low initial viscosity controllable nano-micron particles in Example 1, the core holder was sealed and placed in an oven at 80°C. After aging for 3 days, it was water-driven again to record the breakthrough pressure. At the same time, water-driven was continued until the pressure was stable. The permeability k2 of the core after plugging was measured, and the compressive strength per meter was calculated according to the formula P2=P1×10, and the core plugging rate was calculated according to the formula F=(k1-k2) / k1×100%. The results are shown in Table 1.
[0029] Table 1 Plugging performance of low initial viscosity and controllable nano-micron particles
[0030] From the plugging performance results in Table 1, it can be seen that the low initial viscosity density controllable nano-micron particles involved in the present invention have a plugging rate of greater than 92.5% and a compressive strength of greater than 4.3 MPa / m. After forming a longitudinal chemical barrier interlayer in the deep reservoir, it can effectively prevent the fluids on both sides of the longitudinal chemical barrier interlayer from flowing into each other, thereby achieving the purpose of staged water control in horizontal wells.
[0031] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A low initial viscosity density controllable nano-micron particle for establishing a vertical chemical barrier interlayer in a deep reservoir, characterized in that: The components of the low initial viscosity controllable nano-micron particles and the mass percentage of each component are: Strength control agent 20%~30%; Cross-linking agent 0.05%~0.2%; Initiator 0.1%~0.4%; Density regulator 1%~10%, Remaining amount of water for preparation of liquid.
2. The low initial viscosity density controllable nano-micron particles for establishing a vertical chemical barrier interlayer in a deep reservoir according to claim 1, characterized in that: The strength control agent is a mixture of starch and acrylamide in a mass ratio of 1:1 to 1:
3.
3. The low initial viscosity density controllable nano-micron particles for establishing a vertical chemical barrier interlayer in a deep reservoir according to claim 1, characterized in that: The cross-linking agent is any one or more of phenolic resin prepolymer, chromium acetate or N,N-methylenebisacrylamide.
4. The low initial viscosity density controllable nano-micron particles for establishing a vertical chemical barrier interlayer in a deep reservoir according to claim 1, characterized in that: The initiator is any one or more of ammonium persulfate, acrylate or dibenzoyl peroxide.
5. The low initial viscosity density controllable nano-micron particles for establishing a vertical chemical barrier interlayer in a deep reservoir according to claim 1, characterized in that: The density regulator is any one or more of nano calcium carbonate powder, sodium chloride or hollow glass microspheres.
6. The low initial viscosity density controllable nano-micron particles for establishing a vertical chemical barrier interlayer in a deep reservoir according to claim 1, characterized in that: The preparation water is tap water or on-site injected water.
7. A method for preparing low initial viscosity controllable nano-micron particles for establishing a vertical chemical barrier interlayer in a deep reservoir according to any one of claims 1 to 6, characterized in that: The following steps are involved: (I) under stirring conditions, adding the strength control agent to the heated liquid preparation water in proportion to form a paste-like fluid; (II) under stirring, adding the crosslinking agent, initiator and density regulator in proportion to the paste-like fluid of step (I) in sequence and fully dissolving them; (III) subjecting the mixture obtained by fully dissolving the mixture in step (II) to a cross-linking polymerization reaction to form a high-strength elastomer; (IV) The high-strength elastomer is crushed by a high-speed agitator and further ground by a colloid mill to obtain low initial viscosity and controllable nano-micron particles.
8. The method for preparing low initial viscosity controllable nano-micron particles for establishing a vertical chemical barrier interlayer in a deep reservoir according to claim 7, characterized in that: In the step (I), the temperature of the heated preparation water is 80° C., the stirring speed is 400 rad / min, and the stirring time is 10 min.
9. The method for preparing low initial viscosity controllable nano-micron particles for establishing a vertical chemical barrier interlayer in a deep reservoir according to claim 7, characterized in that: The stirring speed of step (II) is 400 rad / min.
10. The method for preparing low initial viscosity controllable nano-micron particles for establishing a vertical chemical barrier interlayer in a deep reservoir according to claim 7, characterized in that: The temperature of the cross-linking polymerization reaction in step (III) is 80° C., and the reaction time is 8 h to 12 h.
Citation Information
Patent Citations
Screen pipe completion horizontal well shaft and stratum integrated subdivision water control method
CN118065834A
Slow-swelling pre-crosslinked gel volume expansion grains and preparation method thereof
CN102127410A
Pre-crosslinked gel particles for low-temperature reservoir profile control and preparation method thereof
CN109233769A